1997
DOI: 10.1007/bf00941759
|View full text |Cite
|
Sign up to set email alerts
|

Increased intraocular pressure during treatment for chronic uveitis

Abstract: This study demonstrates that a persistent elevation of the IOP in patients suffering from chronic uveitis is, in the majority of cases, associated with the use of corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…14 These contraindications are stressed mainly on prolonged use, and short-term use of DEX treatment is common medical practice. 15 We find that the early application of steroid therapy does indeed produce a minor adverse side-effect, namely the slight delay in corneal erosion healing, but this delay subsided within the first week and seemed to be of no further clinical significance.…”
Section: Discussionmentioning
confidence: 96%
“…14 These contraindications are stressed mainly on prolonged use, and short-term use of DEX treatment is common medical practice. 15 We find that the early application of steroid therapy does indeed produce a minor adverse side-effect, namely the slight delay in corneal erosion healing, but this delay subsided within the first week and seemed to be of no further clinical significance.…”
Section: Discussionmentioning
confidence: 96%
“…Increased VEGF has been reported in eyes with ocular inflammatory disease and in eyes with intraocular malignancy and ischemic retinopathies [11]. In addition, it has been reported that chronic uveitis from various causes is associated with intraocular neovascularization [1]. Because of the characteristic nature of tumors of the NPCE [8], long-standing intraocular inflammation may have relevance to the development of neovascularization on the iris and angle.…”
Section: Discussionmentioning
confidence: 98%
“…The tumor cells in both cases showed negative reactivity for melanoma-specific antigen HMB-45, neuron-specific enolase (NSE 1:50, Dako, Kyoto, Japan) for detecting neuronal differentiation, glial fibrillary acidic protein (GFAP, 1:50, Dako) for detecting glial differentiation, alpha-smooth muscle actin (1:50, Dako) for muscle differentiation. They were positive for S-100 protein (1:2000, Dako) and vimentin (1:50, Dako), which provided support for their origin from the NPCE [1]. They were also positive for cytokeratin KL-1(KL-1, 1:100, Immunotech, Marseilles, France) and cytokeratin CAM 5.2, which are monoclonal antibodies to a large spectrum of cytokeratins.…”
Section: Immunohistochemical Examinationmentioning
confidence: 95%
“…However, up to 27% of affected patients may require surgery as a result of glaucomatous optic neuropathy 21. There are minimal long-term data on the safety or adverse effects of IOP elevation maintained for several weeks, particularly in children, and there may be situations where the patient requires steroid treatment for several months 22. Therefore, weekly monitoring of IOP should be carried out if fluorometholone is to be used in children, particularly in those under 7 years of age 22…”
Section: Discussionmentioning
confidence: 99%